Effects of natural convection flow of fractional Maxwell hybrid nanofluid by finite difference method - Kaleem, Muhammad Mudassar; Asjad, Muhammad Imran; Usman, Muhammad; İnç, Mustafa (Taylor & Francis Ltd, 2023)
Heat transfer phenomenon occurs in a wide range of industrial and engineering problems. In this framework, investigating the heat transfer behavior using an efficient mathematical tool is the hot research area in the research community. Therefore, we discussed the impact of fractional Maxwell hybrid nanofluid on heat transfer under the effects of Joules Heating, Magnetic field, and viscous dissipation via porous Medium with Caputo time fractional derivative. We have considered an infinite vertical wall with adaptable temperature moving with jerked motion along x-direction. Water is taken as base fluid and nano-sized particles of Copper (Cu) & Alumina (Al2O3) are used for the preparation of nanofluid. The governing equations of nonlinear Caputo time fractional model are converted into dimensionless form. A finite difference scheme is developed and applied successfully to get numerical solutions to the problem and to examine the influence of Maxwell hybrid nanofluid, physical parameters, and fractional parameters on velocity and temperature profiles. It can also be observed that the extended finite difference algorithm is very efficient and gives the accurate solution of the discussed model. It can be extended for more numerous types of heat transfer problems arising in physical nature with complex geometry.
Keywords: Maxwell hybrid nanofluid; finite difference scheme; viscous dissipation; joules heating